(untitled) (Comprehensive Journal of Science, 2026)
All praise is due to Allah, abundant, good and blessed praise, and peace and blessings be upon His noble Messenger, sent as a mercy to all mankind. A careful examination of the Qur’an and the Sunnah of the Prophet (peace and blessings be upon him) reveals that Allah and His Messenger have given great attention to human rights and to comprehensive social security, among which food security occupies a central position. Through food security, a person can live in comfort, health, and well-being, free from diseases that disturb life and drain financial resources. This study has clarified the concept of food security both in its general sense and within Islamic law, as well as the risks associated with neglecting its various dimensions—particularly in the agricultural and livestock sectors, which constitute fundamental pillars of integrated food security. This must be preceded by ensuring the availability of a basic element: safe and sustainable water resources. The study also emphasizes the importance of instilling the concept of food self-sufficiency and developing the means to achieve it. It highlights the need to strengthen relations with neighboring countries and others to cooperate in ensuring food security and identifying effective strategies for achieving self-sufficiency. Many scholars have advocated the necessity of working toward practical solutions in order to safeguard human societies everywhere. It is evident that global interest in food security—especially within media discourse—is increasing day by day, aiming to promote a culture of food security and to work toward its realization.